2021
DOI: 10.3233/thc-202673
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transient response of the human foot based on the finite element method

Abstract: BACKGROUND: The foot is an important part of the human body. Its functions are mainly walking and load-bearing. It also keeps the human body stable and absorbs ground vibrations to protect important human organs. OBJECTIVE: Many researchers use finite element methods to study the biomechanics of the foot. However, current studies on the finite element of the foot are based on the stress and displacement response analysis of the foot under static or quasi-static conditions, ignoring the movement process of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
1
0
0
Order By: Relevance
“…Wang et al [72] showed that body weight force (BWF) transmits through the medial metatarsals (1st, 2nd, and 3rd toes and metatarsals), which is in line with the results of peak plantar pressure region in Akrami et al [8] and also in agreement with the outcome of strain energy in foot parts [73]. In addition, Kalra et al [74] showed the important role of medial metatarsals, especially the second ray in BWF transmission by investigating 10 cadaveric feet.…”
Section: Discussionsupporting
confidence: 53%
“…Wang et al [72] showed that body weight force (BWF) transmits through the medial metatarsals (1st, 2nd, and 3rd toes and metatarsals), which is in line with the results of peak plantar pressure region in Akrami et al [8] and also in agreement with the outcome of strain energy in foot parts [73]. In addition, Kalra et al [74] showed the important role of medial metatarsals, especially the second ray in BWF transmission by investigating 10 cadaveric feet.…”
Section: Discussionsupporting
confidence: 53%
“…(MHLW,2019) The human body model referred to is upright, but the knee joint is bent at 90 degrees and adjusted to take into account the length below the knee from under the floor. The material constants of the human body model are determined by referring to the material constants of the analysis simulation (Xiaoying, Liu et. Al., 2022).…”
Section: Human Bodymentioning
confidence: 99%
“…FEM simulation techniques have been used as an effective analytical method to support biomechanical analysis of the human body and have great potential for application in the medical field over the years [19,20]. Furthermore, FEM allows biomechanical modeling and simulation of the soft tissue, bone, and midsole structures of the foot to analyze the deformation, force, displacement, and stress-strain of each tissue structure under different loading conditions, material properties, and boundary conditions [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%